Defining asymptomatic status following sports concussion: fact or fallacy?. Issue 8 (19th May 2011) - Alla, Sridhar; Sullivan, S John; McCrory, Paul
Abstract : The current management of sports concussion involves a return to the baseline 'asymptomatic' status prior to returning to play and training. Unfortunately, although the term 'asymptomatic' is widely used it has not been operationally defined. This review identifies the need to formally define the term 'asymptomatic' as used in sports concussion, discusses some of the challenges associated with its definition and offers some possible solutions for further debate. The operational definition of the term 'asymptomatic' may provide the stimulus for further informed discussion at a future meeting of the international Concussion in Sport group, and by other peak sports medicine bodies involved in management guideline development.